Interfacial bond in concrete-to-concrete composites: A review. (12th December 2022) - Daneshvar, Dana; Behnood, Ali; Robisson, Agathe
Highlights: A state-of-the-art review on interfacial bonds in concrete-to-concrete composites: bonding mechanisms, test methods and influencing factors is presented. Moisture condition, type and properties of adhesive agent, roughness, crossing reinforcement, mismatch in the properties/behavior of concrete layers (including shrinkage), concrete type (UHPC, ECC, RAC, SCC, LWAC), are key factors. Novel materials (sustainable binders, nano-additives, etc), AI techniques and codes are under constant development and should support the continuous improvement of concrete-concrete composite performance and prediction ability of the bond strength. Abstract: Concrete-to-concrete composites have been widely used in a broad range of applications such as buildings, bridges, pavements, dams and tunnels. Numerous studies have been carried out to characterize the structural performance of these composites. This paper presents a state-of-the-art review and key information on the performance of concrete-to-concrete composites. Specifically, design and environmental factors (interface condition, bonding agents, concrete properties, mismatch in overlay and substrate, fibers and admixtures, temperature, humidity) are reviewed and discussed. The test methods developed to determine bond strength under various load combinations are also described. The findings show that a proper selection of overlay and bonding agent composition, interface condition, casting and curing conditions as well as assessment techniques not only result in greater structural performance and durability but also in an optimized material usage and casting cost, leading to a more sustainable approach. Considering the growing application of layered concretes in the recent decade, this review aims at clarifying the parameters that maximize the performance of these composites and at supporting engineers and practitioners in optimizing their composites.